Governing Cotton : Globalization and Poverty in Africa. - Sneyd, Adam (Palgrave Macmillan, 2011)
This book traces the historic relationships between cotton production, the international cotton trade and poverty south of the Sahara, and assesses various approaches to corporate social responsibility and nongovernmental policy advocacy in this area.